A segmentation based analysis for measuring customer satisfaction in maritime transportation - Ekinci, Yeliz; Uray, Nimet; Ülengin, Füsun; Duran, Cem (Transport, 2018)
This study was conducted to profile customers according to the level of satisfaction with the service attributes of maritime public transport provided by Seabus Service Company (SSC), the sole provider of maritime transport in Istanbul. Such analysis needs to be conducted by considering market segments in terms of maritime transportation usage and post purchase behavior. This was accomplished by conducting quantitative research through face-to-face surveys of SSC passengers. According to the results by multivariate data analysis, including factor analysis and cluster analysis, six segments are revealed in terms of customer satisfaction level with the maritime service attributes. Moreover, there are significant differences among the segments in terms of usage frequency (travel frequency in this study), age and education level. Different strategies for different customer segments within the maritime passenger market to increase customer usage and satisfaction of maritime transportation in Istanbul are suggested from the findings. Thus, this paper provides guidelines for the Turkish Maritime Authorities as to how to expand maritime transportation usage in Istanbul, which is not only the largest city and the most crucial trade center of Turkey but also has the highest share of passenger maritime transportation in the country.First published online 24 September 2015